Minerals in the pre-settled coral Stylophora pistillata crystallize via protein and ion changes. Issue 1 (December 2018) - Akiva, Anat; Neder, Maayan; Kahil, Keren; Gavriel, Rotem; Pinkas, Iddo; Goobes, Gil; Mass, Tali
Abstract Aragonite skeletons in corals are key contributors to the storage of atmospheric CO2 worldwide. Hence, understanding coral biomineralization/calcification processes is crucial for evaluating and predicting the effect of environmental factors on this process. While coral biomineralization studies have focused on adult corals, the exact stage at which corals initiate mineralization remains enigmatic. Here, we show that minerals are first precipitated as amorphous calcium carbonate and small aragonite crystallites, in the pre-settled larva, which then evolve into the more mature aragonitic fibers characteristic of the stony coral skeleton. The process is accompanied by modulation of proteins and ions within these minerals. These findings may indicate an underlying bimodal regulation tactic adopted by the animal, with important ramification to its resilience or vulnerability toward a changing environment. Coral biomineralization is an important example of natural mineralization and understanding the process will aid biomineralization research. Here, the authors identify the precipitation of amorphous calcium carbonate and small aragonite crystals in pre-settled larva ofStylophora pistillata.